High Output Heart Failure Secondary Due to Large Arteriovenous Fistula - Kwandou, Willis; Pribadi, Harry; Panda, Agnes Lucia (Universitas Airlangga, 2025)
Background: Arteriovenous fistula (AVF) creation is a commonly performed procedure for patients who suffered from end-stage renal disease (ESRD) and require a permanent vascular access in order to receive long-term hemodialysis. However, these AVF may have a significant deleterious effect on cardiac hemodynamic functions due to increasing cardiac output (CO) and can lead into high output heart failure. Case Summary: Female, 36 years old complained dyspnea on effort, ascites and lower extremity oedema since 6 months ago. She had history of chronic kidney disease and routinely undergoing hemodialysis with brachiocephalic AVF that enlarged since 2 years ago. Physical examination revealed increased jugular vein pressure, hepatomegaly, ascites and giant draining vein of left brachiocephalic AVF with positive Nicoladoni-Branham sign. Echocardiography examination showed dilated right atrium and right ventricle, left ventricle diastolic D-shaped, normal left ventricular ejection fraction with increase right ventricle CO and cardiac index (CI) 7,8 L/minutes/m2, moderate pulmonary regurgitation, severe tricuspid regurgitation (TR) and high probability of pulmonary hypertension. Vascular ultrasound revealed enlarged draining vein with high AVF blood flow rate. Patient then referred to vascular surgeon and decided to undergo ligation of AVF draining vein. After ligation, patient’s right heart failure symptoms were improved and had a better quality of life. upon echocardiography control examination revealed significant improvement of left ventricle diastolic D-shaped. Conclusion: High output heart failure is one of a potential serious complication upon creating AVF hemodialysis vascular access. Routine screening of AVF blood flow rate, identifying high risk patients, and early management is very important to prevent irreversible myocardial damage. – Highlights: 1. This case illustrates that high-output heart failure from an excessively flowing AVF—though rare in younger patients—can be dramatically reversed with AVF ligation, highlighting the importance of flow assessment and timely intervention in dialysis patients with unexplained right heart failure.